STUDI SIFAT MEKANIS TANAH MERAH DENGAN PENGUJIAN TRIAKSIAL - Redaksi Tim Jurnal (FORUM MEKANIKA, 2018)
Characteristics soft soil can cause instability and long-term degradation problems. This is because the soil has a low shear strength value and high compressibility. One type of soil belonging to the soft soil type is soft clay soil. Red soil belongs to the soft clay soil type. Therefore, the purpose of this research to determines the parameters of the shear strength of red soil in the area of Pakjo City Palembang, South Sumatra Province. The equipment had been used to obtain parameters of mechanical properties of red soil was using Triaxial apparatus. The results of the red soil properties index include: water content value (□ 27.70%, specific gravity value (Gs) 2.67, liquid limit value (LL) 66.00%, value of plastic limit of 25.13% and index value (IP) of 40.87% Classification of soil CH (USCS) and A-7-6 (AASHTO). The result of the Triaxial tests was the value of cohesion (c): 16.25-18, 15 kPa, and internal friction (□): 13.50-14.75⁰. The result of shear strength (□) : 17.68-24.02 kPa. The shear strength value of red soil indicates soil which includes soft soil (12.5-25 kPa).